ONLINE ORDER INFORMATION SYSTEM USING WHATSAPP APPLICATION IN ISAL COOKIES BUSINESS - triandini alya; Muhammad Irwan Padli Nasution (JEBS (Journal of Economic and Business Student), 2023)
ABSTRACTThe purpose of this research is to find out the development of an information system for MSME ISAL COOKIES, for example cookies, which will make it easier to provide information such as planning business processes. The research method used by the authors in this study is a quantitative method by collecting data from various aspects needed. such as interviews and documentation. The system that runs on ISAL COOKIES in selling isal cookies products is offering door to door products, consumers still come to the store and see if the product is still available. From the data that has been obtained, the author can conclude that the presence of WhatsApp Business makes it easier for consumers to order cakes, view and select available products. Using WhatsApp Business helps business owners to manage cake sales data records. This WhatsApp Business can provide information about available products, sellers can also update products.Keyworsd: Waterfall, Booking, Appllication, Android